The youth gang problem: a community approach - Spergel, Irving A. (Oxford University Press, 1995)
Introduction : comparative and historical perspectives -- Research limitations : data sources and definitions -- Scope and seriousness of the gang problem -- Gangs, drugs, and violence -- Gang member demographics and gang subcultures -- The structure of the gang -- The gang member experience -- The ecological context -- Youth gangs and organized crime -- Theoretical perspectives -- Planning for youth gang control and violence reduction -- Criminal justice system : the police -- Prosecution, defense, and the judiciary -- Probation, corrections, and parole--after care -- Social intervention -- Social opportunities : education and jobs -- Local community mobilization and evolving national policy